2012
DOI: 10.1242/dev.073056
|View full text |Cite
|
Sign up to set email alerts
|

Islet1 regulates establishment of the posterior hindlimb field upstream of the Hand2-Shh morphoregulatory gene network in mouse embryos

Abstract: SUMMARYHow divergent genetic systems regulate a common pathway during the development of two serial structures, forelimbs and hindlimbs, is not well understood. Specifically, HAND2 has been shown to regulate Shh directly to initiate its expression in the posterior margin of the limb mesenchyme. Although the Hand2-Shh morphoregulatory system operates in both the forelimb and hindlimb bud, a recent analysis suggested that its upstream regulation is different in the forelimb and hindlimb bud. A combination of all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
65
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(74 citation statements)
references
References 66 publications
7
65
0
Order By: Relevance
“…Isl1 was expressed in the ureteric mesenchyme surrounding the base of the ureteric bud stalk and the nephric duct in the wild-type kidneys ( Figure 4E; see also Figures 1 and 3A), which was abolished in the mutant kidneys ( Figure 4F). However, some mutant kidneys showed residual Isl1 expression, as evaluated by immunostaining, probably owing to the mosaic deletion of Hoxb6Cre as reported previously, 9 which could partly explain the variable kidney sizes at E14.5. If the kidney is formed to some extent, hydronephrosis and/or hydroureter could be a prominent phenotype owing to the obstruction at the ureterovesical junction.…”
Section: The Ureter Is Not Properly Connected To the Urinary Bladder supporting
confidence: 51%
“…Isl1 was expressed in the ureteric mesenchyme surrounding the base of the ureteric bud stalk and the nephric duct in the wild-type kidneys ( Figure 4E; see also Figures 1 and 3A), which was abolished in the mutant kidneys ( Figure 4F). However, some mutant kidneys showed residual Isl1 expression, as evaluated by immunostaining, probably owing to the mosaic deletion of Hoxb6Cre as reported previously, 9 which could partly explain the variable kidney sizes at E14.5. If the kidney is formed to some extent, hydronephrosis and/or hydroureter could be a prominent phenotype owing to the obstruction at the ureterovesical junction.…”
Section: The Ureter Is Not Properly Connected To the Urinary Bladder supporting
confidence: 51%
“…The mouse lines for Sall4 (15,40), Gli3 (41), Tcre (21), Hoxb6Cre (22), and Prx1Cre (24) were maintained on a mixed genetic background. Skeletal preparation was done as published (42). Animal breeding and procedures were performed according to the approval by the Institutional Animal Care and Use Committee of the University of Minnesota.…”
Section: Methodsmentioning
confidence: 99%
“…Immunofluorescence of IRX3 (43) and SALL4 (Santa Cruz, sc-101147, 1/300 dilution) was performed on cryo-sections according to standard procedures (42). Simultaneous cell proliferation and cell death analyses were performed by using anti-phospho histone H3 (Upstate, catalog no.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…None of the numerous combinations of posterior Hox loss-offunction mutants reported to date (9)(10)(11)(12)(13)(14) are known to lead to hindlimb AP patterning defects analogous to those reported for loss of Hox9 or Hox5 paralogs. Itou et al (53) recently demonstrated that LIM-homeodomain factor Islet1 is a critical regulator of Hand2 expression and the posterior compartment in hindlimbs. How the hindlimb anterior compartment is established remains to be discovered.…”
Section: Discussionmentioning
confidence: 99%